Penguatan Eduwisata Sejarah Lokal Lampung melalui Pelatihan Pemandu Wisata bagi Mahasiswa Pendidikan Sejarah - Triaristina, Aprilia; Rachmedita, Valensy; Ekwandari, Yustina Sri (Pakis Journal Institute, 2026)
This community service program aims to strengthen the local historical edu-tourism in Lampung through tourism guide training for History Education students. Historical edu-tourism serves as a medium to introduce and educate the public about the historical and cultural values embedded in historical sites. Lampung, as a province rich in historical sites, has great potential to develop educational tourism destinations that can attract tourists and raise awareness of the importance of cultural preservation. This training was held in two main sessions: the first session provided theoretical understanding of historical edu-tourism and the potential historical sites in Lampung, as well as effective historical tour guiding techniques; the second session focused on field practice, where students were trained to become competent tour guides by using storytelling techniques and digital media to enrich the tourist experience. Students were equipped with skills to present historical narratives in an engaging and interactive manner, as well as to utilize technology to make the tour more dynamic and informative. Through this training, students are expected to actively contribute to the development of the historical tourism sector in Lampung, by applying the knowledge they gained in historical tour guiding and contributing to efforts to preserve local cultural heritage. This community service program also aims to raise public awareness of the importance of historical edu-tourism as part of educational tourism, which can provide economic benefits while introducing the cultural values of Lampung to the outside